Sensory function, cognition, and brain structure in SCD, MCI, and AD: Initial findings from the COMPASS‐ND Study: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Phillips, Natalie; Al‐Yawer, Faisal; Giroud, Nathalie; Rehan, Sana; Pappadatos, Zoe; Mick, Paul; Wittich, Walter; Pichora‐Fuller, M. Kathleen
Abstract: Background: There is a strong relationship between sensory and cognitive function in older adults and impairment in hearing, vision, and olfaction are each independently associated with dementia. However, these have rarely been examined together in persons with dementia, nor their concurrent relationship with cognitive function and brain structure. The Comprehensive Assessment of Neurodegeneration and Dementia (COMPASS‐ND) study is a large‐scale study of older Canadians who are living with, or are at risk for, dementia, including those with subjective cognitive decline (SCD), mild cognitive impairment (MCI), Alzheimer's disease (AD), other causes of dementia, and normal controls. We collect clinical and cognitive data, structural brain imaging, and measures of sensory function. Method: Complete sensory, cognitive, and brain imaging data have been released on participants with study diagnoses of SCD (n=35; 74% women, mean age = 69.4 years; mean education = 16.6 years), MCI (n=79; 49% women, mean age = 73.5 years; mean education = 15.5 years), and AD (n=21; 10% women, mean age = 75.9 years; mean education = 15.5 years). Hearing function was assessed by pure tone screening at 25 and 40 dB and with a computerized speech in noise perception task. Vision function was assessed by measuring reading acuity and contrast sensitivity. Olfaction was assessed with a 16‐item olfactory recognition test. Result: Controlling for age, sex, and education, cognitive performance measures decreased over the groups (SCI>MCI>AD), as expected. The groups differed in contrast sensitivity and olfaction, but not hearing (audiometric category, perceiving digits in noise) or visual reading acuity. Poorer olfaction was associated with poorer auditory episodic memory and lower hippocampal volume. Poorer hearing thresholds were associated with lower right hippocampal volume in SCD participants. Within MCI participants, poorer hearing was associated with a disruption in the relationship between auditory episodic memory and a number of variables, including visual episodic memory and lateralized hippocampal volume. Conclusion: These results illustrate a complex interplay between sensory‐cognitive‐brain measures in older adults with or at risk for dementia and suggest that sensory status has important implications for brain structure and clinical status.